The Chemistry of Unusually Functionalized Azides - Banert, Klaus (Synthesis, 2016)
This short review describes the synthesis and reactions of organic azides bearing an adjacent additional functional group, such as azidoacetylenes, α-azido alcohols, geminal azidohalo compounds, formyl azide, 1,1-diazidoethenes, and azidocyclopentadienes. Some of these compounds were extensively investigated in previous quantum chemical studies, but experimental access was missing until quite recently; other such azides were simply overlooked for a long time. The title compounds are able to undergo a variety of intramolecular and intermolecular subsequent reactions, which can find application in synthetic chemistry.1 Introduction2 Ethynyl Azides3 Geminal Azidohalo Compounds and α-Azido Alcohols3.1 Azidohalomethanes3.2 Discovery and Synthesis of α-Azido Alcohols3.3 Reactions of α-Azido Alcohols4 Formyl Azide5 1,1-Diazidoethenes6 Azidocyclopentadienes7 Conclusion and Outlook
Keywords: azides; cycloaddition; hazardous compounds; low-temperature NMR spectroscopy; photolysis; reactive intermediates; trapping reactions